passer 2020
DOI: 10.24271/psr.07
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Students’ Mental Health in the University of Garmian Using the Kurdish General Health Questionnaire

Abstract: It is predicted that Kurdish people, especially in Garmian District, face more mental health issues due to war, displacement and numerous political conflicts. On the other hand, different studies showed that mental health of university students decreases during their educational years. So, this study aimed to investigate the mental health of students in University of Garmian, using the Kurdish General Health Questionnaire (K-GHQ). In this cross-sectional study sample consists of 156 students selected by multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…Researches suggested that people who live in Kurdistan region, generally have more mental health issues due to experiencing conflicts, displacement, violence, and political upheavals. 14,24 The results of this study also confirm this claim, because the total scores of mental health for non-quarantined group is also higher than the cut-point.…”
Section: Demographic Characteristicssupporting
confidence: 77%
See 1 more Smart Citation
“…Researches suggested that people who live in Kurdistan region, generally have more mental health issues due to experiencing conflicts, displacement, violence, and political upheavals. 14,24 The results of this study also confirm this claim, because the total scores of mental health for non-quarantined group is also higher than the cut-point.…”
Section: Demographic Characteristicssupporting
confidence: 77%
“…13 Findings by local researchers are in agreement with these reports. 14,15 In addition to ongoing stressors and the weak health system, stigma is a major barrier for the population to seek mental health services in the region. 16 When not addressed, these stressors and problems will have long-term impact on the population.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a study regarding the general health of the students of the University of Garmian, which is located in Kalar, using the same questionnaire. In the mentioned study, it was reported that more than 90% of the participants achieved higher scores than the cutoff point, and the highest scores also belonged to the subscales of anxiety, insomnia, and social performance (23). On the other hand, another study in this regard indicated that more than 80% of the participants had social phobia (24).…”
Section: Discussionmentioning
confidence: 92%
“…Bunlar içinden daha ucuz, uygulaması daha kolay, geçerli ve güvenilir olan standart anketler genellikle İngilizce dışındaki dillere de çevrilmiş ve uygulanmıştır. Bu araçlar, sağlık ve tıp görevlilerine daha az maliyetli ve daha az zaman alan bir şekilde güvenilir bilgi sağlama yeteneğine sahiptir (Seidi, 2020).…”
Section: öZel Bir Grup Olarak üNiversite öğRencileriunclassified
“…2020 yılına kadar tüm dünyada toplam hastaların %15'ini oluşturan ruhsal ve sinirsel bozuklukların oranının %50'ye kadar artması beklenmektedir. Ruhsal bozukluklardaki bu çarpıcı artış, kardiyovasküler hastalıklardaki artıştan bile daha yüksek olacaktır (Seidi, 2020).…”
Section: Introductionunclassified